Program Layanan Bimbingan Klasikal dengan Media Audiovisual untuk Meningkatkan Motivasi Belajar Siswa pada Masa Pandemi Covid-19 : Literature Review - Elvia Khoiriyah; Zulfatul Azizah; Abdul Muhid (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2021)
Counseling guidance has a variety of services for students who experience problems in school or their learning activities at school. However, during a pandemic like this both teachers and students have to adjust. Teachers must make innovations to continue to provide the best possible service so that various problems faced by students during this pandemic period can be resolved properly. Counseling guidance services are divided into two, namely classical guidance services and individual guidance services. Classical services are services provided by counseling teachers to students in the number of class units or can be interpreted as a guidance service provided by guidance and counseling teachers / counselors to a number of students in class units carried out in the classroom. Besides being easy to implement, this service can also be used using certain media. And with this service, time is used more efficiently in motivating students in terms of learning. This research is a literature study or literature review where the researcher conducts an assessment of previous studies. Keywords: Classical Guidance service; Audio Visual Media; Motivation to learn; The covid-19 pandemic